Proceedings of the V National Meeting of the Italian Group of Paleopathology (GIPaleo) - V.V., A.A. (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2019)
Editor: Luca Ventura - Division of Pathology, San Salvatore Hospital, L’Aquila, Italy Lecture The wound and the leg amputation of Giovanni dalle Bande Nere (1498-1526): life and death of a mercenary captain of the italian renaissance - G. Fornaciari Session 1 Chairmen: L. Saragoni (Forlì) e G. Ercolani (Forlì) Session 2 Chairmen: E. Rabino Massa (Torino) e M. Licata (Varese) Session 3 Chairmen: M. Traversari (Forlì) e R. Gaeta (Pisa) Session 4 Chairmen: L. Ferrari (Asti), E. Fulcheri (Genova)